2001
DOI: 10.1002/jca.1011
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusion therapy

Abstract: The relative merits of apheresis platelets and platelet concentrates are undergoing debate due to evolving issues of safety, inventory, and cost. The application of photochemical inactivation technology may eliminate any rationale for the use of apheresis platelets rather than pooled platelet concentrates, so that the relative merits of these two alternatives will be debated over costs and inventory. Doses of apheresis platelets are determined by donor platelet count and by platelet yield. The generation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…undertaken to increase the yield of apheresis platelet product, 2 and our studies have demonstrated that a recombinant thrombopoietin might also be of benefit. 3,4 Exposing healthy donors to hematopoietic growth factors has long been controversial, as has the concept of exposing donors to apheresis devices themselves.…”
Section: Thrombopoietin In Healthy Donorsmentioning
confidence: 85%
See 2 more Smart Citations
“…undertaken to increase the yield of apheresis platelet product, 2 and our studies have demonstrated that a recombinant thrombopoietin might also be of benefit. 3,4 Exposing healthy donors to hematopoietic growth factors has long been controversial, as has the concept of exposing donors to apheresis devices themselves.…”
Section: Thrombopoietin In Healthy Donorsmentioning
confidence: 85%
“…Rather, we think that their results are in accord with well-established knowledge of the factors involved in ADPinduced TxA 2 generation: (1) ADP does not stimulate TxA 2 production directly; (2) it is the close platelet-to-platelet contact that is brought about by ADP-induced platelet aggregation that triggers the production of TxA 2 ; and (3) this effect is greatly enhanced and can be seen in most healthy individuals when [Ca ϩϩ ]o is decreased to micromolar levels. [2][3][4][5] Based on this interpretation, it is not surprising that the experiments performed by Jin et al showed that antagonists of P2Y 1 , P2Y 12 , or the fibrinogen receptor, which inhibit ADP-induced platelet aggregation, abolished the TxA 2 production. The dependency of TxA 2 production and the ensuing platelet secretion on platelet aggregation is demonstrated by the observation that no TxA 2 production or platelet secretion occurs from normal human platelets that are stimulated by ADP, even at high concentration, under conditions in which platelet aggregation does not occur: for instance, if the receptor function for adhesive proteins on ␣ IIb ␤ 3 is inhibited with inhibitory monoclonal antibodies or Arg-Gly-Asp-containing peptides, or, more simply, if the platelet suspension is not stirred.…”
Section: Adenosine Diphosphate (Adp) Does Not Induce Thromboxane a 2 mentioning
confidence: 93%
See 1 more Smart Citation
“…Good quality platelets obtained by qualified operators from whole blood and from apheresis with properly performed methods show similar ability in preventing and resolving hemorrhage episodes secondary to thrombocytopenia or thrombocytopathy (25). In spite of the expected and appealing advantages offered by apheresis, which derive from decreased donor exposure as compared to platelet transfusion with concentrates from whole blood units, a clear demonstration of the cost‐effectiveness of this approach in the recent peer‐reviewed scientific literature on transfusion medicine is not available (25). Theoretically, it appears that apheresis, through the reduction of donor exposure, could reduce the number of transfusion‐transmitted infections (26) and recipients developing antibodies to human leukocyte antigens (HLA), a family of antigens present on platelet membrane.…”
Section: Preparation and Quality Control Of Platelet Concentratesmentioning
confidence: 99%
“…The number of platelet concentrates or equivalents transfused in the United States escalated from 7,335,000 in 1989 to 9,040,000 in 1997 [1]. Controversies still surround the optimal platelet dose (PD).…”
Section: Introductionmentioning
confidence: 99%